Bayesian essentials and bayesian regression - Rossi, Peter (Henry Stewart Talks, 2010)
The goal of inference, Bayes theorem, Decision theory, Sampling properties of Bayes estimators, Costs and benefits of Bayes, Conjugate families, Beta-binomial model, Bayesian regression, IID simulator, Shrinkage and conjugate priors